2018
DOI: 10.1136/bmjopen-2018-025896
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient centredness through patient-reported experience measures (ASPIRED): protocol of a mixed-methods study

Abstract: IntroductionThe impact of patient centredness (PC) in healthcare has grown over the years. However, conceptualisations of PC are heterogeneous. Existing patient-reported measures of PC have shown inconsistencies and shortcomings. This impedes the comparison of results across studies. To foster PC, it is important to know which dimensions matter most to patients and to be able to measure its current extent from the patients’ perspective. This study aims (1) to assess relevance of dimensions of PC from the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Concerning the number of experts necessary when using this methodology, there is no established consensus, although a number of experts of around 10 is usually considered sufficient to be considered valid [53,54]. In our case, the number of experts was nine, which we consider to be sufficient, considering the heterogeneity of the sample [55]. The high rate of agreement achieved after the consultation rounds, and the fact that all the domains and subdomains were recognized as being relevant, without suggestions for further items to be included on behalf of the experts, helps support the validity of the instrument content.…”
Section: Discussionmentioning
confidence: 93%
“…Concerning the number of experts necessary when using this methodology, there is no established consensus, although a number of experts of around 10 is usually considered sufficient to be considered valid [53,54]. In our case, the number of experts was nine, which we consider to be sufficient, considering the heterogeneity of the sample [55]. The high rate of agreement achieved after the consultation rounds, and the fact that all the domains and subdomains were recognized as being relevant, without suggestions for further items to be included on behalf of the experts, helps support the validity of the instrument content.…”
Section: Discussionmentioning
confidence: 93%
“…This Delphi study was conducted as part of the study ‘Assessment of patient-centeredness through patient-reported experience measures (ASPIRED) 22. Within the study ASPIRED, a patient-reported experience measure will be developed to foster PC care.…”
Section: Introductionmentioning
confidence: 99%
“…While efforts have been made to collect and measure information about the patient experience using qualitative studies or surveys, actions and strategies on systematically improving quality of care and promoting patient-centered care according to patient-reported experience measures have not yet been fully undertaken [ 67 ]. Considering the positive correlation between the patient experience and clinical outcomes, it needs to be considered as a tool to refine the quality of care and enhance the implementation of the concept of patient-centeredness [ 18 , 64 , 68 ]. In a recent study evaluating key drivers of the patient experience in pediatric population with heart disorders, cheerfulness during practice, the cohesiveness of staff, and explanation of problems and conditions from the providers were identified as predictive of overall satisfaction [ 69 ].…”
Section: Discussionmentioning
confidence: 99%